AMERICAN CULTURAL VALUES REFLECTED IN THE AMERICAN MASTERCHEF SEASON 5 IN 2014 = Các giá trị văn hóa của mỹ được phản ánh qua chương trình vua đầu bếp Mỹ mùa thứ 5 năm 2014 - Nguyễn, Thị Loan (2020)
The study realizes the reflection of American cultural values in American Mastechef season 5 and some implications of making use of this reality show to teach and learn about intercultural communication. Qualitative approach is used to help the researcher collect an in-depth understanding of people's behaviour and language use in the chosen episode. Observation is the main data collection instrument. The process of data collection includes three phases: selecting and recording the episode transcribing and watching, observing and taking notes and comparing the check list of the American cultural values in theoretical background.There are two stages in data analysis procedure: identifying the American cultural values and analysing these values in details. The finding shows that 10 out of 11 values discussed in theoretical background, are revealed in the reality show. Particularly, there are 3 values reflected in the languistic and cultural aspects used by judges including directness and openness, equality of opportunity and informality and 10 values reflected in the languistic and cultural aspects used by contestants consisting of directness and openness, individual freedom, competitiveness, hard work, future orientation, informality, self- reliance, equality of opportunity and practicality and efficency, time and its control. From these findings, the author also suggests American Masterchef as an authentic teaching material to the study of foreign language and intercultural communication an meaningful resource for English learners.